Design and Simulation of a Rectangular Solar Collector for the Green Tower Development / Zainoor Hailmee Solihin ...[et al.] - Solihin, Zainoor Hailmee; Wisnoe, Wirachman; Zailani, Ramlan; Yusof, Noriah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Solar chimneys generally have large size solar collectors. This is because of the solar chimney output is directly proportional to the input. The more solar energy is harvested, the higher the output. Aside from the size, most of a big solar collector is in a cylindrical shape. Thus, this study proposes the role of solar collectors which has a rectangular build at a smaller size and known as Green Towers. The main purpose of this study is to determine the performance of the rectangular solar collectors for Green Tower development. This report presents the numerical simulation and validates with the field experiment of the Green Tower. Various analyses were carried out for investigating the Green Tower performance and the result was very promising. The resulting air velocity increases with various geometrical sizes of the Green Tower. In summary, using the rectangular shaped solar oven’s collector has significantly increased the temperature distribution for the Green Tower thus improve its efficiency and overall performance.